Analisis Sistem Kepribadian Dan Sistem Keluarga Terhadap Suksesi Bisnis UKM - Syarifuddin Syarifuddin; M. Arpah; Mohammad Aras; Muhammad Sapuan (Manajemen Kreatif Jurnal, 2025)
This investigate points to look at the impact of the identity framework (identity framework) and family framework (family framework) on commerce progression. The populace in this investigate are SMEs in Batam. The test taken in this inquire about was 48 respondents utilizing the coincidental review strategy. The explanatory apparatus utilized is different direct relapse with the assistance of the SPSS 25 program. The comes about gotten in this inquire about appear that the personality system (identity framework) includes a positive and noteworthy impact on business progression.